Comprehensive evaluation of spring barley mutants according to their yield components - A. A. Belozerova; D. A. Bazyuk; N. A. Bome (Труды по прикладной ботанике, генетике и селекции)
Background. The need to increase the genetic diversity of barley (Hordeum vulgare L.) is determined by its value and cultivation scope, which is especially important in the context of the changing climate.Material and methods. The study was carried out in 2021 and 2022 at the experimental site of the Lake Kuchak biostation located in Nizhnetavdinsky District, Tyumen Province (57°20ʼ57.3”N, 66°03ʼ21.8”E). Mutant forms were obtained by treating seeds of accessions ʻZernogradsky 813ʼ, Dz02-129 and C.I. 10995 with solutions of the chemical mutagen phosphemide at concentrations of 0.002% (2·10–3 М) and 0.01% (1·10–2 М). The mutants of the fifth (M5) and sixth (M6) generations were evaluated for a set of traits valuable for breeding in comparison with the original forms and reference cultivars ʻAchaʼ and ʻAbalakʼ. The main productivity characters were analyzed in the laboratory, and breeding indices were calculated (ear potential index, Canadian index, ear linear density index, Mexican index, plant productivity index, and Finnish-Scandinavian index).Results and conclusion. Most of the studied mutants under moisture deficit and elevated temperature conditions were superior to the original forms in their productivity characters. Mutant plant samples with stable manifestation of those traits, irrespective of the growing season conditions, were selected. Assessment of the genotype–environment interaction using breeding indices made it possible to identify promising mutants for inclusion in breeding programs. Correlation analysis helped to identify indices closely related to grain yield: Canadian index (r = 0.85), Mexican index (r = 0.76), and plant productivity index (r = 0.70). They can be recommended for selection of stress-resistant barley forms.